Towards the Integration of Genome Scale Models and Bioreactors for the Production of Commodity Chemicals - Lázaro Ibáñez, Jorge; Júlvez, Jorge (Jornada de Jóvenes Investigadores del I3A, 2021)
Most processes for the production of commodity chemicals rely on fossil fuels, and hence, are highly pollutant. A promising alternative is to develop bioprocesses that make use of genetically engineered cells. A novel modeling framework is proposed to speed up the overall design of bioprocesses and optimize their productivity.